The Causes of Civil War - Djankov, Simeon; Reynal-Querol, Marta (World Bank, Washington, DC, 2012)
The dominant hypothesis in the literature that studies conflict is that poverty is the main cause of civil wars. The authors instead analyze the effect of institutions on civil war, controlling for income per capita. In their set up, institutions are endogenous and colonial origins affect civil wars through their legacy on institutions. Their results indicate that institutions, proxied by the protection of property rights, rule of law and the efficiency of the legal system, are a fundamental cause of civil war. In particular, an improvement in institutions from the median value in the sample to the 75th percentile is associated with a 38 percentage points' reduction in the incidence of civil wars. Moreover, once institutions are included as explaining civil wars, income does not have any effect on civil war, either directly or indirectly.